Mentoring Programs for Novice Teachers in Kazakhstani Mainstream Schools: Experiences and Attitudes of Main Stakeholders - Karimova, Nazerke (Nazarbayev University Graduate School of Education, 2020)
Kazakhstan faces teacher shortages and teacher attrition, despite government efforts to increase the prestige of the teaching profession. High teacher attrition rates for novice teachers are attributed to the lack of support available, which can be addressed by the provision of mentoring programs. However, there is a lack of knowledge about mentoring programs for novice teachers in the context of Kazakhstan. The purpose of this study is to explore the components of mentoring programs for novice teachers through the main stakeholders’ experiences and attitudes in Kazakhstani mainstream schools. This qualitative study used semi-structured individual and focus group interviews to collect data from 21 participants at two sites. Sites and participants were recruited using purposeful sampling and the collected data were analyzed using thematic analysis. The study presents the mentoring programs purposes, organization, structure, and main stakeholders' relationships derived from the experiences and attitudes of three types of participants: school administrators responsible for a mentoring program, mentors, and novice teachers as mentees. The findings revealed that mentoring offers professional guidance to mentees who are actively involved in the process. There are formal and informal mentoring types co-existing in schools which use a variety of mentoring approaches. Mentors were allocated based on years of teaching experience and evidence of continuous professional development. No training was provided for the role. The content of the mentoring programs was flexible to meet the needs of mentees, but with a common focus on teaching and bureaucratic issues. Mentors provided feedback rather than assessment of mentees. The study makes recommendations for policymakers and school administrators about the addition of formal mentor training and the content of mentoring programs.
Keywords: mentoring novice teachers; mentors; Kazakhstan; mentoring program